Online Learning: Strategies to Improve Critical Thinking Skills on PAI Learning In School - Yanuar Wicaksono; Agus Zaenul Fitri; Abd. Aziz (Journal of Contemporary Islamic Education, 2022)
This study aims to explain the implementation of online learning and teacher strategies in improving students' critical thinking skills in PAI subjects at SMPN 1 Sumbergempol Tulungagung and SMPN 3 Tulungagung. The research method is qualitative. The research approach is phenomenological. The type of research is field research. The research design was a multi-site study. Data were obtained by in-depth interviews, participant observation, and documentation. The research data is then organized into categories, described into units, synthesized, arranged into patterns, selected priority data, and made conclusions so that they are easy to understand. The results showed that WhatsApp, Telegram, Google Classroom, Zoom, Google Meet, One Drive, Google Form, and Microsoft Office 365 teachers were integrated. The strategy used by the teacher is to design learning and implementation of learning that directs critical thinking. The teacher sharpens thinking levels from C1, C2,3 to C4, C5, C6. The task given is to find material from the internet and analyze it. Students will use critical, analytical, comparative, selective and creative reasoning.